Treatment of multiple network parameter errors through a genetic-based algorithm - Stacchini de Souza, Julio C.; Do Coutto Filho, Milton B.; Meza, Edwin B. Mitacc (Electric power systems research, 2009)
This paper proposes a genetic algorithm-based methodology for network parameter estimation and correction. Network parameter errors may come from many different sources, such as: imprecise data provided by manufacturers, poor estimation of transmission lines lengths and changes in transmission network design which are not adequately updated in the corresponding database. Network parameter data are employed by almost all power system analysis tools, from real time monitoring to long-term planning. The presence of parameter errors contaminates the results obtained by these tools and compromises decision-making processes. To get rid of single or multiple network parameter errors, a methodology that combines genetic algorithms and power system state estimation is proposed. Tests with the IEEE 14-bus system and a real Brazilian system are performed to illustrate the proposed method.